173 BONE ALLOGRAFT FAILURE IN THE MUSCULOSKELETAL TUMOR SETTING: HOST IMMUNE RESPONSE TO FOREIGN HUMAN LEUKOCYTE ANTIGEN. Issue 1 (1st January 2007) - Sousa, T.; Cizik, A.; Nelson, K.; Eary, J.; Conrad, E. U.
Abstract : Purpose: The human leukocyte antigen (HLA) molecule is a highly polymorphic gene involved in both acute and chronic rejection of large organ transplants and thought to be involved with nonunion and rejection of bone allografts. The purpose of this study was to examine if foreign HLA sensitization to a bone allograft results in graft complications. Study Methods: We analyzed 86 patients' serum using flow cytometry to detect anti-HLA class I and II IgG antibodies. We defined "major complications" as those that resulted in either the removal of the allograft or complications that showed graft nonunion. Statistical analysis included chi-square test for categorical data, and allograft survival was estimated using Kaplan-Meier survival analysis. Results: Of the 86 patients, 32 (37%) had a major complication resulting in the revision of the allograft union site. Graft survival was 71% at 2 years, 56% at 5 years, and 44% at 10 years, with a mean survival of 86 months. Fifty-eight patients (67%) had production of HLA class I or class II antibodies. Patients with deep infection had an increased rate of major allograft complications compared with those without a deep infection (60% vs 40%, p = .01). In the absence of infection, 93% of patients (14/15) with a negative immune response had no major complications ( p = .02). Also, 39% of patients (18/46) with a positive immune response had a major complication ( p = .02). Conclusion: Infection and HLA immune response are two factors that contribute to complications, which result in nonunion with the host bone. If infection to the site can be minimized, then minimizing the immune response will also contribute to higher success rates.